CONСЕPTS АND THЕORIЕS IN TRАNSLАTION - Rashidov, Sanjar (Журнал иностранных языков и лингвистики, 2023)
This paper examines the role of concepts and theories in translation. Furthermore, wide variety of translations and history of translation. Provided article discusses integral components of translation. Incorporating analysis-based evidence is given accomplishments in science of translation, thus types of translation.